THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN EDUCATION - Normurodova Madina Akmal qizi,; Tursunova Munisa Timur qizi,; Alimkhanova Nigorakhon Amilevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article explores the role of artificial intelligence in modern education, providing a detailed analysis of its importance, applications, advantages, and future potential.AI is fundamentally transforming the education system by shaping how and what we teach, offering solutions tailored to various challenges, and enhancing overall learning experiences.The article also discusses both the benefits and drawbacks of AI in education. The author concludes that while AI is a powerful tool in modern teaching, it cannot replace the human element and the role of the teacher.